Paul's gospel in Romans : a discourse analysis of Rom. 1:16-8:39 - Lee, Jae Hyun. (Linguistic Biblical Studies, 2010)
This book offers a fresh approach to Paul's gospel. Applying linguistic discourse analysis to Romans 1:16-8:39, it helps the reader to gain a comprehensive understanding of the argumentative structure and contents of the gospel of Paul. As well as revealing the two underlying descriptive frameworks that Paul uses to explain his gospel about God's salvation - the interactive framework between God and humans, and the 'two-realm' framework - this book demonstrates that Paul's gospel consists of one 'peak point' that shows the central role of Jesus, and two 'sub-peaks' elucidating salvation.